The Rationality of Community Actions and Islamic Educational Values in the Megengan Tradition In Jabon Village - Moh. Hanif Adzhar (International Journal of Religion and Social Community, 2024)
This article aims to examine the rationalisation of the Megengan tradition practised by the community of Jabon Village, Kediri Regency. The Megengan tradition in this village has its distinctive features, particularly with the mandatory offering of gedhang rojo (a type of banana) and Apem cake during the practice. This study employs a qualitative case study method, with data collected through interviews with informants and a review of relevant literature, including articles and books. Using Max Weber's theory of social action and the concept of Verstehen (interpretive understanding), the study seeks to describe the rationality behind the community’s participation in the Megengan tradition. The findings reveal that the tradition is upheld to preserve and continue the routine practices of the ancestors. From the perspective of instrumental rationality, the aim of engaging in the Megengan tradition is to carry it out according to the financial capacities of each household. In terms of value-rationality, the act of offering food as charity reflects gratitude, and the prayers recited symbolise faith in Allah (SWT). Thirdly, in affective action, sharing food with neighbours demonstrates strong emotional ties and serves as a means of nurturing community bonds. Finally, the Megengan tradition embodies Islamic educational values, such as ukhuwah Islamiyah (brotherhood), charity, gratitude, empathy, and tolerance.